Break-Even Point Analysis of Micro, Small, and Medium Enterprises (MSMEs) Producing Sasirangan Fabric in Sasirangan Village, Banjarmasin - Rukman, Rukman; Bintari, Endah Sri; Sucidha, Irma; Nirwana, Ros (Journal of Business & Applied Management, 2025)
This study aims to analyze the break-even point (BEP) as a tool for profit planning in the Sasirangan Cloth Micro, Small, and Medium Enterprises (MSMEs) located in Sasirangan Village, Banjarmasin. Using a quantitative descriptive approach, data were collected through observation and documentation supported by financial records of the enterprise. The analysis involved classifying costs into fixed, variable, and semi-variable categories, followed by BEP calculation in both units and monetary terms, as well as contribution margin, margin of safety, and profit planning analysis. The findings indicate that the enterprise reaches its break-even point at sales revenue of Rp. 54,042,553 or 1,633 units sold. The Contribution Margin Ratio (CMR) was found to be 47%, while the Margin of Safety (MOS) reached 53%, suggesting a relatively strong buffer against sales decline. Furthermore, in order to achieve a targeted profit increase of 5%, the MSME must generate revenue of Rp. 333,202,381, equivalent to 6,336 units sold. The implication is that BEP analysis can serve as a simple yet powerful instrument for MSMEs in traditional industries, enabling better decision-making, sustainability, and competitiveness in local and regional markets.